2022
DOI: 10.1055/a-1944-9718
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Aerobic Oxidation of Tertiary Silanes to Silanols using Molecular Oxygen as an Oxidant

Abstract: The photocatalyzed synthesis of silanols from tertiary silanes has been carried out using eosin Y under air. This is a metal-free method which uses a low catalyst loading, atmospheric oxygen as the oxidant, and visible light conditions (blue light).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…First, the activation of rose bengal, then interacts with Most recently, Gui and coworkers found the oxidation of hydrosilanes to silanols could be achieved by using eosin Y as the photocatalysis. [87] The reaction was performed using O 2 as the oxidant under blue light irradiation. an array of monohydrosilanes converted into the desired silanols in high yields (27 examples, 71-99 % yields) (Scheme 47).…”
Section: Photoorganocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…First, the activation of rose bengal, then interacts with Most recently, Gui and coworkers found the oxidation of hydrosilanes to silanols could be achieved by using eosin Y as the photocatalysis. [87] The reaction was performed using O 2 as the oxidant under blue light irradiation. an array of monohydrosilanes converted into the desired silanols in high yields (27 examples, 71-99 % yields) (Scheme 47).…”
Section: Photoorganocatalysismentioning
confidence: 99%
“…Most recently, Gui and coworkers found the oxidation of hydrosilanes to silanols could be achieved by using eosin Y as the photocatalysis [87] . The reaction was performed using O 2 as the oxidant under blue light irradiation.…”
Section: Metal‐free Catalytic Hydroxylation Of Hydrosilanesmentioning
confidence: 99%
“…The employed catalysts are organocatalyst or Cs base, manganese catalyst, and iron catalyst . Recent atypical approaches for silanol synthesis include the electrochemical transformation, while photocatalytic reactions are also widely employed . As a new trend, Arnold recently reported an enzymatic oxidation of hydrosilanes using evolved enzyme …”
Section: Introductionmentioning
confidence: 99%
“…With the development of photoredox catalysis in the last decade, the photo-induced oxidation of silane has also progressed significantly ( Scheme 1 c) [ 34 , 35 , 36 , 37 ]. In 2021, Chen, Fan, and their colleagues reported that under the irradiation of white light, Ru(bpy) 3 Cl 2 could catalyze the formal dehydrogenative reactions between silanes and water to produce silanols [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Wang reported that the conversion of silanes to silanols could be accomplished using Rose Bengal as a photocatalyst, oxygen as an oxidant, and water as an additive [ 37 ]. Subsequently, He and Zhang reported the conversion of silane to silanol using eosin Y as a photocatalyst [ 34 ]. The study of photoinduced synthesis of silanol inspired us to consider whether the photocatalyst aminoquinolate B,B-diphenyl complex AQDAB [ 39 , 40 ], which was developed by our group and applied in photooxidation reactions [ 40 , 41 , 42 ], could induce such transformations.…”
Section: Introductionmentioning
confidence: 99%